Are D-manno-configured Amadori products ligands of the bacterial lectin FimH? - Gloe, Tobias-Elias; Stamer, Insa; Hojnik, Cornelia; Wrodnigg, Tanja M.; Lindhorst, Thisbe K. (Beilstein Journal of Organic Chemistry, 2015)
The Amadori rearrangement was employed for the synthesis of C-glycosyl-type D-mannoside analogues, namely 1-propargylamino- and 1-phenylamino-1-deoxy-α-D-manno-heptopyranose. They were investigated as ligands of type 1-fimbriated E. coli bacteria by means of molecular docking and bacterial adhesion studies. It turns out that Amadori rearrangement products have a limited activity as inhibitors of bacterial adhesion because the β-C-glycosidically linked aglycone considerably hampers complexation within the carbohydrate binding site of the type 1-fimbrial lectin FimH.
Keywords: Amadori rearrangement; bacterial adhesion; C-mannosides; docking studies; FimH ligands